Development of a Digital Game-Based Learning Tool to Foster Environmental Conservation Awareness - Paitoon, Nuttapong; Phophet , Chankrit; Sungkaew, Kornchulee (Journal of Applied Statistics and Information Technology, 2025)
This research aimed to design and develop a digital game to foster environmental conservation awareness among upper primary school students. The game, titled “Plant More Trees,” was created using Scratch 3.0 and consisted of 12 progressive levels involving tasks such as watering, fertilizing, and protecting trees from pests. The objective was to integrate environmental knowledge and promote sustainable behavior through interactive gameplay. The game was tested with 71 students from Grades 4 to 6. The results showed a statistically significant increase in environmental knowledge after gameplay, with high levels of satisfaction reported by the participants (average satisfaction scores of 4.19 - 4.30). The findings indicate that Plant More Trees is an effective learning tool for instilling environmental awareness in children and holds potential for use in modern educational contexts.